2017
DOI: 10.1136/archdischild-2017-313777
|View full text |Cite|
|
Sign up to set email alerts
|

Early academic achievement in children with isolated clefts: a population-based study in England

Abstract: ObjectivesWe used national data to study differences in academic achievement between 5-year-old children with an isolated oral cleft and the general population. We also assessed differences by cleft type.MethodsChildren born in England with an oral cleft were identified in a national cleft registry. Their records were linked to databases of hospital admissions (to identify additional anomalies) and educational outcomes. Z-scores (signed number of SD actual score is above national average) were calculated to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 22 publications
3
75
2
Order By: Relevance
“…In our work, the percentage of children with NS OFCs receiving special education services ranged from 35% in third grade to 29% in fifth grade. These estimates are consistent with previous work in both the United States and Internationally which reported 20–29% of children with NS OFCs across multiple ages and grade levels were enrolled in special education services (Fitzsimons et al, ; Wehby et al, ; Yazdy et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our work, the percentage of children with NS OFCs receiving special education services ranged from 35% in third grade to 29% in fifth grade. These estimates are consistent with previous work in both the United States and Internationally which reported 20–29% of children with NS OFCs across multiple ages and grade levels were enrolled in special education services (Fitzsimons et al, ; Wehby et al, ; Yazdy et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Among children with NS OFCs who were receiving services, 44–55% of children with NS OFCs across third, fourth, and fifth grade were placed for special education services under the speech and language eligibility category with 16–22% of children being placed under the specific learning disability category. This estimate is marginally lower than other studies which reported 74–86% of children with NS OFCs were placed for services under the speech and language impairment exceptionality (Fitzsimons et al, ; Yazdy et al, ). In Yazdy's work, the mean age of entry into special education among children with NS OFCs was 6 years of age.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Specifically, children with CPO are at higher risk of underperforming in several areas of academic learning, compared to both their unaffected peers, and also children born with CLO or CLP 52 . On the contrary, children born with CLO have been found to have academic achievement higher than children born with CLP or CPO 15 and sometimes 53 (though not always 13,15 ) in-line with children born without a cleft.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…Interestingly however, achievement scores were similar between affected children and their unaffected siblings 14 . In the most recent population-based study, 2,802 five-year-old children born with a non-syndromic cleft in England had lower average academic achievement across all learning domains compared to national averages 15 .…”
Section: Introductionmentioning
confidence: 94%